THE INFLUENCE OF YOUTUBE CONTENT ANDREW KALAWEIT ON ENVIRONMENTAL AWARENESS AMONG GENERATION Z - Ramadhan, Rafael Rizqi; Hadi, Sigit Pramoon (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
Currently, it is undeniable that social media is being enjoyed by people of all age groups, including Gen Z, on an almost hourly and even minute basis. Social media serves as a platform for individuals to interact with others, creating, sharing, exchanging, and modifying ideas through virtual communication. In Indonesia, YouTube has become a popular and favored social media platform. One of the YouTube accounts that has gained significant popularity is Andrew Kalaweit's account. Andrew Kalaweit is a Youtuber who focuses on nature conservation and has become an influential figure in this field. This research adopts a descriptive quantitative methodology with a positivism paradigm. The sampling method used in this study is non-probability sampling technique and purposive sampling method. The purpose of this research is to examine the impact of Andrew Kalaweit's YouTube content on the environmental care attitudes of Generation Z. The results of the simple linear regression analysis indicate that Y = 12.617 + 0.794X, with a significance value of 0.000, based on the findings of the conducted research. This study demonstrates that Andrew Kalaweit's YouTube account has a positive influence on the environmental care attitudes of Gen Z.